Physicochemical, conformational and functional properties of silver carp myosin glycated with konjac oligo-glucomannan: Implications for structure-function relationships. (November 2017) - Liu, Jianhua; Luo, Yahong; Gu, Saiqi; Xu, Qiuhong; Zhang, Jingjing; Zhao, Peicheng; Ding, Yuting
Abstract: Silver carp myosin (Ms) was glycated with konjac oligo-glucomannan (KOG) under dry reaction conditions. The physicochemical properties (amino acid composition, total sulfhydryl groups, hydrophobicity, viscosity and microstructure), conformational properties (heat changes, secondary and tertiary conformations) and functional properties (emulsifying properties) were investigated. The amino acid composition (especially relative acidic/basic charged amino acid ratio) was an intrinsic physicochemical parameter that largely determined other physicochemical and conformational properties. Formation of Ms-KOG conjugates reduced the total sulfhydryl groups content and hydrophobicity. Glycation for 12 h increased the viscosity of Ms by 35-fold. Nanoscale structure and secondary conformation, as determined by atomic force microscopy and far-UV circular dichroism spectroscopy, remarkably changed. Combined analysis of differential scanning calorimetry and intrinsic emission fluorescence indicated that Ms may undergo a tertiary conformation unfolding and subsequent rearrangement process. More importantly, we have interestingly found that KOG improved the flexibility in conformation and enhanced the steric hindrance of Ms. This specific structure of Ms-KOG eventually improved the emulsifying properties. Graphical abstract: Highlights: Ms-KOG reduced the total sulfhydryl groups content and hydrophobicity. Glycation with KOG for 12 h increased the viscosity of Ms by 35-fold. Ms undergoes a conformational unfolding and rearrangement process during glycation. The EAI and ESI of Ms were significantly increased after glycation with KOG. KOG improved the flexibility in conformation and enhanced the steric hindrance of Ms.